Identification and Mapping of HBsAg Loss-Related B-Cell Linear Epitopes in Chronic HBV Patients by Peptide Array - Gu, Shuqin; Liu, Zhipeng; Lin, Li; Zhong, Shihong; Ma, Yanchen; Li, Xiaoyi; Ye, Guofu; Wen, Chunhua; Li, Yongyin; Tang, Libo (Frontiers in Immunology, 2021)
Identification of immunogenic targets against hepatitis B virus (HBV)-encoded proteins will provide crucial advances in developing potential antibody therapies. In this study, 63 treatment-naïve patients with chronic HBV infection and 46 patients who achieved hepatitis B surface antigen loss (sAg loss) following antiviral treatment were recruited. Moreover, six patients who transitioned from the hepatitis B e antigen-positive chronic infection phase (eAg+CInf) to the hepatitis phase (eAg+CHep) were enrolled from real-life clinical practice. Additionally, telbivudine-treated eAg+CHep patients and relapsers or responders from an off-treatment cohort were longitudinally studied. The frequencies and function of B cells were assessed by flow cytometry. We devised a peptide array composed of 15-mer overlapping peptides of HBV-encoded surface (S), core (C), and polymerase (P) proteins and performed a screening on B-cell linear epitopes with sera. Naïve B cells and plasmablasts were increased, whereas total memory, activated memory (AM), and atypical memory (AtM) B cells were reduced in sAg- patients compared with sAg+ patients. Importantly, longitudinal observations found that AtM B cells were associated with successful treatment withdrawal. Interestingly, we identified six S-specific dominant epitopes (S33, S34, S45, S76, S78, and S89) and one C-specific dominant epitope (C37) that reacted with the majority of sera from sAg- patients. Of note, more B-cell linear epitopes were detected in CHep patients with alanine aminotransferase (ALT) flares than in nonflare CInf patients, and five B-cell linear epitopes (S4, S5, S10, S11, and S68) were overwhelmingly recognized by ALT flare patients. The recognition rates of epitopes on C and P proteins were significantly increased in CHep patients relative to CInf patients. Strikingly, a statistically significant elevation in the number of positive epitopes was observed when ALT nonflare patients shifted into the flare phase. Moreover, S76 identified at baseline was confirmed to be associated with a complete response after 48 weeks of telbivudine therapy. Taken together, we identified several functional cure-related B-cell linear epitopes of chronic HBV infection, and these epitopes may serve as vaccine candidates to elicit neutralizing antibodies to treat HBV infection.